192 USING A COLLABORATIVE APPROACH TO IDENTIFY WAYS TO STRENGTHEN ENHANCED CARE PRACTICES IN A GENERAL HOSPITAL WHILE BUILDING RESEARCH CAPACITY. (18th November 2021) - Daly, L; White, P; Harris, E; Carroll, A F; Murphy, A
Abstract: Background: The Nursing department within an acute general hospital wished to illuminate and build on positive local enhanced care practices. A collaborative research team was formed between academics in the linked higher education institution and nurses within the hospital to address this intent by building nurse-led research capacity, while addressing the practice derived research question. Methods: A mixed methods approach was employed involving; site visits, audit of enhanced care staffing requirements, documentary and activity box analyses and use of appreciative inquiry (AI) methodology. AI is a collaborative and strengths-oriented approach supporting organisational development. It was implemented via three World Café events (www.theworldcafe.com 2021) bringing together hospital stakeholders (n = 17) with direct experience of delivering enhanced care, to consider pre-defined questions. Thematic analysis was used to analyse the resultant data. Ethical approval was obtained. Results: Overall, the findings demonstrated a positive focus on implementing therapeutic enhanced care within the hospital in contrast to a more passive primarily observational orientation. The site visits facilitated shared learning. Thematic findings from the World Cafés identified positive care practices and enabled a multidisciplinary, inclusive approach, which facilitated pragmatic suggestions on how to plan for, and build on existing foundations of, enhanced care practice. Conclusion: Both the study approach and outcome resulted in positive impacts. Working collaboratively supported research capacity building for hospital-based members of the research team. Using AI supported constructive and inclusive stakeholder participation in the World Cafés with a focus on good practices and ways in which they could be strengthened. One year post completion, study recommendations have led to: Use of 'enhanced care' as the vocabulary of choice for hospital staff Six bedded bays previously referred to as 'Special Bays' renamed as 'Enhanced Care Bays' A 'Therapeutic Enhanced Care Policy' to support practice has been developed and is at review stage Enhanced care-related documents have been reviewed.